Association between statin use and 30-day mortality among patients with sepsis-associated encephalopathy: a retrospective cohort study - Chen, Junwei; Chen, Junde; Li, Lihong (Frontiers in Neurology, 2024)
AimSepsis-associated encephalopathy (SAE) is a common and serious complication of sepsis with poor prognosis. Statin was used in SAE patients, whereas its effects on these patients remain unknown. This study is aimed at investigating the impact of statins on the 30-day mortality of patients with SAE.MethodsIn this retrospective cohort study, data from SAE patients were extracted from the Medical Information Mart for Intensive Care IV (MIMIC-IV). Statins include atorvastatin, pravastatin, rosuvastatin, and simvastatin. The outcome was 30-day mortality of SAE patients starting 24 h after the first intensive care unit (ICU) admission and at the first time after hospitalization. Potential covariates (sociodemographic characteristics, vital signs, score indexes, laboratory parameters, comorbidities, and treatment intervention methods) were selected using univariate Cox proportional hazard analysis. Associations between statin use and statin type and 30-day mortality were explored using univariate and multivariate Cox proportional hazard models with hazard ratios (HRs) and 95% confidence intervals (CIs). Associations were further explored in different age groups, sex, sequential organ failure assessment (SOFA), simplified acute physiology score II (SAPS II), and systemic inflammatory response syndrome (SIRS) populations.ResultsA total of 2,729 SAE patients were included in the study, and 786 (28.8%) died within 30 days. Statin use was associated with lower odds of 30-day mortality (HR = 0.77, 95%CI: 0.66–0.90) in all SAE patients. Patients who took simvastatin treatments were associated with lower odds of 30-day mortality (HR = 0.58, 95%CI: 0.43–0.78). Rosuvastatin treatments had a higher 30-day mortality risk (HR = 1.88, 95%CI: 1.29–2.75). Statin use was also associated with lower 30-day mortality among patients of different ages, sex, sequential organ failure assessment (SOFA), SAPS II, and SIRS.ConclusionPatients who were treated with simvastatin were associated with lower odds of 30-day mortality in SAE patients. Caution should be paid to statin use in SAE patients, particularly in patients treated with rosuvastatin or pravastatin.